Sosialisasi Tentang Gizi Seimbang Pada Anak Sekolah Dasar Negeri 12 Sungai Pinang Kecamatan Sambas - Wahyu; Amira; Anggraini; Ariska; Ayu Febby Puspita; Mia Talia; Novia Pipit Kurniawati; Rendi Agustian (Hippocampus: Jurnal Pengabdian Kepada Masyarakat, 2022)
Elementary school students are an age group that is vulnerable to nutrition. This is due to the rapid growth and development of children and relatively busy school schedules. Optimization of development in children requires adequate nutrition from the point of view of quality and quantity and requires attention in terms of stakeholders. Children of primary school age are at risk of having nutritional problems related to nutrition, growth and development. The main purpose of this socialization is to provide knowledge to students about the importance of balanced nutrition in children of primary school age. The method used in this activity is storytelling. During the socialization period, the students were very enthusiastic, many asked questions and there was a two-way communication. The provision of nutrition education on storytelling and singing methods went smoothly at SDN 12 Sungai Pinang. Follow-up is needed regarding socialization activities for the implementation of student diets with balanced nutrition.